Content analysis of advertisings in Turkish banking industry - KARAPINAR, EKİN (My University, 2017)
Banking industry, which is one of the most important elements of services industry in Turkey, has been developed rapidly due to the influence of recent developments in information and communications technologies (Örs; 2003, p.6; Taşkın et al., 2010, p.11). Concordantly, changes in consumer demands and needs in the banking industry, importance of bank preference and buying behavior in this sector has increased competition (Taşkın et al., 2010, p.12; Doğru et al., 2013, p.53). Banks in a rapidly developing competitive environment has enhanced advertising insights, which is one of the factors that determines how a bank is perceived and how it is required to be perceived as a brand. They also started to use classical communication as well as modern communication technologies (Mylonakis, 2008, p.44; Demir, 2013, p.2; Edwards, 2017, p.24). According to the research company McKinsey & Company's Global Media Report, total global media expenditures, which is 1.6 trillion dollars in 2014, are composed of 38,7% television commercials, 28,2% internet ads and 18,9% newspaper and magazine advertisements2. Consumer financing companies in USA are among the top industries that invest the most in advertising followed by banking, health services and alcoholic beverages industry3. According to the data from the members of the Advertising Association, media investments in Turkey, which was $ 1,830 million in the first half of 2014, reached $ 3,518 million at the end of the year4. Media investments are composed of 52% television and 19,4% printed media. Among printed media, total annual circulation is composed of 94,1% newspapers5. Finance, insurance, communication and e-commerce sectors are indicated as driving force of this growth6. By 2005 the industries that advertise the most in Turkey are food, personal care, beverage, household cleaning products and finance industry7. It is determined that advertising investments in the banking and finance industries have been increasing since 2009 (Çelik, Dinçer and Yılmaz, 2012, p.54). Nielsen Media announced that 18 banks were on the “2012 largest advertisers list”8. The report which was broadcasted by the Media Monitoring Center in October 2015 indicated that finance industry was the seventh on the list which shows the industries give advertising on TV by unit, and banking-finance ads were the fourth on the list in terms of durationsecond9. In recent years, it is stated that in particular, public banks have invested more than 1 billion TL in their advertising investments in televisions and in newspapers10. Within this context, the purpose of the study is to investigate whether newspaper advertisement contents of banks in Turkey differ based on banks‟ capital structures and fields of activity. For this purpose, “content analysis” is used. The banks were chosen by using the statistics of the Banks Association of Turkey (2014) and were defined as the first two banks in terms of asset for each type11. In one yaear, it has been analysed totally 151 advertising campain of eight banks of four different types (foreign banks, private banks, public banks, interest-free banks) in two different newspapers, which are selected with the highest number of subscribers and circulation. Analyses were carried out in terms of media planning, advertising content, compatibility with the page where the content was published and adverting message. It is found that advertising contents differ based on the capital structures of the banks. In terms of media planning, private banks use regular schedule planning; however, it differs between other banks. After analyzing the compatibility with the page and the message in newspaper advertisements for four different types of banks, it was discovered that there was integrity for all types of banks. It was found that there was difference between bank types considering the advertising messages of banks.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Pazarlama; Social Sciences and Humanities; Management; Marketing; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities